Métodos variacionais em problemas de termoelasticidade acoplada - Gonzáles Guirnaldos, Castor (1977)
The present work is dueto obtain the aproximate solution of the equations in couple thermoelasticity. We are going to de velop the teory of the problem, later we plana variational approach of the equations, afterward we are going to obtain numerical results with support of the finite elements method.